PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA TONGKONAN BASSE KABUPATEN ENREKANG (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study  purposed to find out how the influence the leadership of the villange head had on community participation in development in Tongkonan Basse villange,Enrekang Regency.The This study used descriptive quantitative.The data analysis technique used simple linear regression bu using SPSS software version 24.0 The results showed that the leadership of the villange head had a significant effect on community participation.This was indicated by the value of t count > t tabel with a value of 4.436 > 1.986 with a significant value of 0.000 < 0.05.Based on the coefficient of determination  (R Square) of 0.176,which meant the influence of village head leadership (X)             on community participation (Y) was 17.6%, while the residual was influenced by other factors.